Preferences for physical and virtual retail formats choice - Maçik, Radosłav (Managing global transitions, 2014)
Paper discusses Polish consumers% behaviour and preferences for retail channel and format choice on the background of relevant literature. Results include perception maps created using multidimensional scaling (mds) on data from two studies: in 2008 and 2012, giving possibility to assess changes at the economic slowdown. Two-dimensional solutions are fitting the data very well and allow to describe compared formats in terms of perceived level of personal interactions with the sales personnel, and perceived total cost for consumer. During analysed period perception of discount stores substantially changed - previously perceived as similar to marketplace, now they are closer convenience stores. Virtual channel formats are still perceived as separate cluster in comparison to physical ones. Declared shopping frequency for 15 formats from both channels is compared with emotional attitudes toward them. In addition, unianova procedure has been used to find connections with shopping frequency and demographic variables as well as decision-making styles
Keywords: prodaja; retail format choice; consumer preferences; kupci; demografija; demography; economic slowdown; decision-making styles; načini odločanja; nakupno vedenje; Poland; Poljska; demographics